Inactivation of Escherichia coli O157:H7 in Poultry Chiller Water Using Combined Ultraviolet Light, Pulsed Electric Field and Ozone Treatments - Ngadi, Michael; Jun, Xue; Smith, James; Raghavan, G.S.V. (International Journal of Poultry Science, 2004)
A laboratory study was conducted to assess the efficacy of using combination of ultraviolet light (UV) irradiation, pulsed electric field (PEF), and ozone for inactivation of Escherichia coli O157:H7 in poultry chiller water. The E. coli cells showed high resistance when ozone was used alone in the study. Only about 0.6 log reduction was obtained at the ozone dose of 1 mg/ml of sample after 30 s contact time. UV treatment for 1 min at the intensities of 117 and 234 mW/cm2 resulted in 2 and 3.5 log reductions, respectively. When the sample was treated with 200 pulses of electric field at 23 and 30 kV/cm, E. coli inactivation was 3.5 and 4.1 log, respectively. Combinations of ozone, UV and PEF yielded additional inactivation effect that was essentially sum of the different inactivation levels obtained separately for the different hurdles. Inactivation increased with increase in intensity of the treatments. For the treatment conditions studied, combined treatment using UV and PEF resulted in higher inactivation of E. coli O157:H7 in poultry chiller water.